Gut Microbiota Linked with Reduced Fear of Humans in Red Junglefowl Has Implications for Early Domestication. Issue 4 (9th December 2021) - Puetz, Lara C.; Delmont, Tom O.; Aizpurua, Ostaizka; Guo, Chunxue; Zhang, Guojie; Katajamaa, Rebecca; Jensen, Per; Gilbert, M. Thomas P.
Abstract: Domestication of animals can lead to profound phenotypic modifications within short evolutionary time periods, and for many species behavioral selection is likely at the forefront of this process. Animal studies have strongly implicated that the gut microbiome plays a major role in host behavior and cognition through the microbiome–gut–brain axis. Consequently, herein, it is hypothesized that host gut microbiota may be one of the earliest phenotypes to change as wild animals were domesticated. Here, the gut microbiome community in two selected lines of red junglefowl that are selected for either high or low fear of humans up to eight generations is examined. Microbiota profiles reveal taxonomic differences in gut bacteria known to produce neuroactive compounds between the two selection lines. Gut–brain module analysis by means of genome‐resolved metagenomics identifies enrichment in the microbial synthesis and degradation potential of metabolites associated with fear extinction and reduces anxiety‐like behaviors in low fear fowls. In contrast, high fear fowls are enriched in gut–brain modules from the butyrate and glutamate pathways, metabolites associated with fear conditioning. Overall, the results identify differences in the composition and functional potential of the gut microbiota across selection lines that may provide insights into the mechanistic explanations of the domestication process. Abstract : Domestication of animals can lead to profound phenotypic modifications and for many species behavioural selection is likely at the forefront of this process. Gut microbiota are known to play an active role in host behavior. Differences in gut microbiota features are identified across red junglefowl selected for divergent fear towards humans that might provide further insights into the domestication process.